Fenomena Kehidupan Remaja Yatim/Piatu di Dusun Sendang Biru Kabupaten Malang - Alfiana Yuli Efiyanti; Esa Nur Wahyuni (Universitas Kanjuruhan Malang, 2019)
Young generation, especially teenagers, plays a very important role in the nation's sustainability. However, it becomes hard situation for orphan teenagers as they live in abnormal situations. In Sendang Biru, Sumbermanjing Wetan Malang, orphan teenagers experience problems that occur due to their orphan status. There are various social problems, that relating to economic and psychological problems. Continuously attention and assistance has been provided by the community through the social community “An Nisa”. However, because the assistance is short-term and momentary, it only touches a small number of problems faced, and has not touched other psychological and social domains. We strongly recommend Sendang Biru community, government and higher education institutions to develop long-term programs that can solve the whole problems of orphan teenagers in Sendang Biru.